The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1051/rnd:19780702
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of monoamine oxidase control by thyroxin in the heart, brain and brown adipose tissue of the developing rat

Abstract: Summary. The aim of the present work was to determine whether the increase in monoamine oxidase activity previously found in hyper-and hypothyroid rats, was due to thyroxin effects on enzymatic activity or to variations in enzyme synthesis.The rate of synthesis of monoamine oxidase in young hyper-and hypothyroid rats has been studied by measuring the recovery of enzymatic activity 7 days after irreversible inhibition by Pargyline. Hyperthyroidism was followed by an increase in the rate of synthesis of monoamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
1984
1984

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…In this respect, it appeared interesting to study their effects in few steps involved in catecholamine physiology of the developing rat. In previous papers, we described the influence of the thyroid status on the development of monoamine oxidase (4,5) and catechol-omethyltransferase (6) activities in different organs of the young rat.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, it appeared interesting to study their effects in few steps involved in catecholamine physiology of the developing rat. In previous papers, we described the influence of the thyroid status on the development of monoamine oxidase (4,5) and catechol-omethyltransferase (6) activities in different organs of the young rat.…”
Section: Introductionmentioning
confidence: 99%
“…During the same period, hypothyroidism induces an increase in the activities of both MAO and COMT, while hyperthyroidism has the opposite effect on MAO. We have already shown that the increase in MAO activity following hypothyroidism in BAT of the young rat is the consequence of an increased synthesis rate of the enzyme (9).…”
Section: Discussionmentioning
confidence: 99%